Student’s Perception on The Role of Youtube Videos as a Learning Sources for Improving their Vocabulary Skill in Senior High School - Dyah Ayu Febri Ananda; Rizki Nurfida Pambayun; Imro’atul Husna (Edusaintek)
The selection of appropriate learning media can enhance students' academic performance. YouTube, as the largest video-sharing platform in the world, can serve as an effective alternative learning medium. This research aims to explore students' perceptions of using YouTube as a learning resource to improve English vocabulary skills. Students often feel bored with monotonous teaching methods, making audiovisual media an appealing solution. The study was conducted at a high school in Rogojampi with eleventh-grade students, employing a qualitative descriptive method. Data were collected through questionnaires and interviews to facilitate analysis. The results indicate that students responded positively to the use of YouTube in English learning, particularly in vocabulary enhancement. Students felt more interested and motivated due to the varied and visually engaging educational videos, and they recommended YouTube as a medium for learning English.